Microvesicles and Cancer Associated Thrombosis - Lacroix, Romaric; Vallier, Loris; Bonifay, Amandine; Simoncini, Stephanie; Mege, Diane; Aubert, Mathilde; Panicot-Dubois, Laurence; Dubois, Christophe; Dignat-George, Françoise (Seminars in Thrombosis and Hemostasis, 2019)
Microvesicles (MVs) are small membrane enclosed structures released into the extracellular space by virtually all cell types. Their composition varies according to the cell origin and the stimulus which caused their formation. They harbor functional molecules and participate in intercellular communication. Endothelium, inflammatory cells, and cancer cells produce procoagulant MVs which contribute to cancer-associated thrombosis (CAT) in animal models. The tissue factor (TF) conveyed by these MVs was shown to play a key role in different animal models of experimental CAT. Alternatively, other molecular mechanisms involving polyphosphates or phosphatidylethanolamine could also be involved. In clinical practice, an association between an increase in the number of TF-positive or the procoagulant activity of these MVs and the occurrence of CAT has indeed been demonstrated in pancreatic-biliary cancers, suggesting that they could behave as a biomarker predictive for CAT. However, to date, this association was not confirmed in other types of cancer. Potential causes explaining this limited associated between MVs and CAT are (1) the diversity of mechanisms associating MVs and different types of cancer; (2) a more complex role of MVs in hemostasis integrating their anticoagulant and fibrinolytic activity; and (3) the lack of sensitivity, reproducibility, and standardization of current methodologies permitting measurement of MVs. Each of these hypotheses constitutes an interesting exploration path for a future reassessment of the clinical interest of the MVs in CAT.
Keywords: extracellular vesicles; microvesicles; cancer-associated thrombosis